2018
DOI: 10.1007/s00702-017-1837-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic targets for the treatment of l-DOPA-induced dyskinesia

Abstract: Dopamine (DA) replacement therapy with L-3,4-dihydroxyphenylalanine (L-DOPA) continues to be the gold-standard treatment for Parkinson's disease (PD). Despite clear symptomatic benefit, long-term L-DOPA use often results in the development of L-DOPA-induced dyskinesia (LID), significantly reducing quality of life and increasing costs for PD patients and their caregivers. Accumulated research has demonstrated that several pre- and post-synaptic mechanisms contribute to LID development and expression. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 153 publications
1
28
0
1
Order By: Relevance
“…Recent efforts have focused on modulating the serotonin system in an attempt to regulate abnormal dopamine release in the striatum and prevent the development of dyskinesia ([ 35 ] for a recent review). Several groups have investigated the use of selective serotonin reuptake inhibitors (SSRIs) and serotonin (5-HT) receptor agonists in combination with L-DOPA treatment (e.g., [ 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts have focused on modulating the serotonin system in an attempt to regulate abnormal dopamine release in the striatum and prevent the development of dyskinesia ([ 35 ] for a recent review). Several groups have investigated the use of selective serotonin reuptake inhibitors (SSRIs) and serotonin (5-HT) receptor agonists in combination with L-DOPA treatment (e.g., [ 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest are especially 5-HT1A receptor agonists (e.g., [ 14 , 18 , 37 , 38 , 39 , 43 , 44 ]), which are thought to stimulate 5-HT1A autoreceptors on serotonin neurons in the dorsal raphe nucleus (DRN) and attenuate neuronal activity and, consequently, serotonin (and abnormal dopamine) release from serotonin terminals. Many of the serotonergic agents tested are indeed found to reduce dyskinesia severity in preclinical studies [ 35 ]; however, these agents can also attenuate the prokinetic effects of L-DOPA or have other undesirable side effects (e.g., [ 42 , 45 , 46 , 47 ]), limiting their clinical usefulness [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dosi handiagoek ez zituzten emaitza hain onuragarriak lortu; izan ere, OFF aldien emendioarekin erlazionatu ziren, efektu antidiskinetiko gehigarririk aurkeztu gabe [15]. Hala ere, iaz argitaratutako eskala handiagoan egindako bi ikerketatan, 2 mg-ko dosiak ez zuen erakutsi plazeboarekin konparatuz ezberdintasunik [16].…”
Section: Aurrerapen Terapeutikoak Parkinson Gaixotasuneanunclassified
“…The serotonin (5-HT) system has been demonstrated to play a crucial role in the pathogenesis of LID in animal models of PD [79]. Indeed, after advanced dopaminergic cell loss, remaining serotonin neurons can convert exogenous LD to DA and mediate its vesicular storage and release [38,80].…”
Section: Serotonin Receptorsmentioning
confidence: 99%
“…5-HT 1A R is the most studied of the 5-HT family. Indeed, several preclinical and clinical studies demonstrated that 5-HT 1A R stimulation (auto- and heteroreceptors) [49,83,84] may reduce dyskinesia through the decrease of DA release [79]. Moreover, 5-HT 1A R activation may also weaken glutamatergic transmission ameliorating motor symptoms [83].…”
Section: Serotonin Receptorsmentioning
confidence: 99%